Cows - Green, Emily K. (Minneapolis, MN : Bellwether, 2007)
Simple text and illustrations introduce young readers to cows on a farm.
K-3.
Includes bibliographical references and index.
19
Keywords: Dairy cattle; Cattle; Domestic animals; Dairy cattle; Cattle; Domestic animals